Lu-Hf ISOTOPIC SYSTEMATICS AND THIER APPLICATIONS IN PETROLOGY - Wu F.Y.; Li X.H.; Zheng Y.F.; Gao S. (My University, 2007)
Lu-Hf is one of the isotopic dating and geochemical tracing techniques developed very rapidly during the past years. This paper presents a comprehensive review about the history, geochemical applications in petrology and remained problems surrounding the Lu-Hf isotope system. An overall introduction to the presently used sample digestion, mass spectrometric measurement and laser in-situ ablation techniques is also provided. The development of Hf isotopic systematics can be divided into 3 stages of TIMS, hot-SIMS and MC-ICP-MS, but the advent of MC-ICPMS accelerates their applications in petrology. After presenting the foundmantal geochemical behaviour and principles of the Lu-Hf isotope, this paper reviews its applications in petrology in details, including the isotopic dating of the garnet- and apatite-beraing rocks, early continental crustal formation and evolution, nature and petrogenesis of different mantle end-members, identification of various magmatic processes, regional geodynamic evolution and Hf isotopic variance during metamorphism. Finally, we discuss the uncertainties of 176Lu decay constant, Hf isotopic ratios of commonly used standards of solution JMC475 and zircon/baddeleyite, and closure temperature of Hf isotopic systems.
Keywords: LU-HF ISOTOPE; PETROLOGY; WHOLE-ROCK; ZIRCON